Orbital Clinicopathological Differences in Thyroid Eye Disease: An Analysis of Cytokines With Histopathological and Clinical Correlation - Li, Yue; Tang, Jiaqi; Jing, Gaojing; Li, Yueyue; Ma, Rui; Kang, Xin; Rong, Liyuan; Liu, Wenlu; Yao, Lan; Lv, Xiaohui; Deng, Aijun; Wu, Wei; et al. (Investigative ophthalmology & visual science, 2025)
To explore the pathological differences in orbital adipose/connective tissue between active and inactive thyroid eye disease (TED) subjects and their correlations with clinical characteristics. Orbital adipose/connective tissue samples from 42 TED subjects (20 active, 22 inactive) were collected during decompression surgery. We analyzed cytokine expression, inflammatory cell infiltration, inherent cell populations, and interstitial changes by Luminex and histopathology. Correlations were analyzed using Pearson and Spearman correlation analyses. Among the 108 cytokines detected, active TED exhibited elevated platelet endothelial cell adhesion molecule 1 (PECAM-1), interleukin-23 (IL-23), a proliferation-inducing ligand (APRIL), IL-6, C-C motif chemokine ligand 2 (CCL2), β-nerve growth factor (NGF), and lower CCL21 and CCL5. The extent of infiltration by helper T (Th) cells and monocytes was significantly greater in the active group than in the inactive group. Adipocyte density was significantly elevated in active TED, whereas fibrosis was more prominent in inactive TED. Fifteen cytokines were significantly associated with inflammatory cell infiltration, with IL-16 showing the strongest correlations with T cells. Ten cytokines showed significant positive correlations with fibrosis. Four cytokines (IL-6, PECAM-1, IL-23 and transforming growth factor β1), Th cell infiltration and adipocyte density were significantly positively correlated with clinical activity score (CAS). Sixteen cytokines, along with adipocyte density, were significantly positively correlated with disease severity of TED. The orbital adipose/connective tissues of active and inactive TED subjects showed significant differences in terms of cytokines, inflammatory cells infiltration, inherent cells and interstitium. These pathological changes were correlated with clinical characteristics of TED.